POLA PRODUKSI DAN FAKTOR-FAKTOR YANG MEMENGARUHI PEMBELIAN DAGING SAPI OLEH PRODUSEN BAKSO DI KOTA BANDAR LAMPUNG - Afsani Saputri; Raden Hanung Ismono; Wuryaningsih Dwi Sayekti (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2019)
The aims of this study were to analyze the pattern of meatballs production, find out the patterns purchase of beef and analyze the influencing factors on  beef purchase by meatball producers in Bandar Lampung. This research was conducted by survey method in Bandar Lampung.  Research data was collected from October to December 2016 and analyzed by descriptive and multiple regression analysis. The samples consisted of 45 meatball producers who were drawn by simple random sampling method. Results of this research showed that the production pattern on meatball producers in Bandar Lampung was as follows: producing filled meatballs, pure meatballs, tofu meatballs, and egg meatballs, in which frequency of production and purchase of beef were every day. The average of beef purchase was 69 kilograms per week.  The influencing factors on the purchase of beef by the meatball producers in Bandar Lampung were the amount of meatballs production. Key words: beef, producer of meatballs, purchasing pattern